Use of the functional independence measure in Japanese rehabilitation team interaction. (December 2019) - Izumi, Hiroaki
The functional independence measure (FIM) is a clinical scale which is used to evaluate the amount of assistance disabled persons need to conduct their daily living activities. Drawing on 65 video-recorded rehabilitation team meetings and medical records collected from a Japanese hospital, this article utilizes ethnomethodology and conversation analysis to uncover how Japanese rehabilitation team members use the FIM to track changes in the functional status of patients and decide the length of stay in ongoing interactional sequences. Analysis shows that a series of the FIM scores assembled and arranged in situ provide a sequential framework for members to understand the progress of rehabilitation and predict the plateau phase. Moreover, a particular expert is asked about patients' capacity for further improvements and his or her opinions are treated as a basis for clinical decisions. In this way, diagnostic and clinical decision-making is produced through the ongoing collaborative work of various specialists.